Ecological dynamics of stink bugs that attack soybean and corn ﬁelds in the Neotropical region - Rodrigues, Hígor de Souza (2021)
Soybean and corn are the two most representative crops of Brazilian agribusiness. However, during the crop development cycle factors such as pest insect attack, especially the Neotropi- cal brown stink bug, Euschistus heros, and the green belly stink bug, Diceraeus melacanthus, can reduce productivity and require care. Thus, tools to compose an integrated pest management (IPM) program become necessary to minimize the losses caused by these arthropods. Based on that, this thesis was constructed with the objectives of evaluating the competitive ability of E. heros and D. melacanthus, verifying the toxicity of different insecticide groups and the detoxiﬁ- cation capacity of these insects under different temperatures and generating products (ie, maps of suitability) that indicate safer locations with greater risk of cultivation in the face of attack by these two pentatomids based on the current climate, thus generating preventive control tools for a bed bug MIP program. Euschistus heros was more competitive than D. melacanthus since the presence of its heterospeciﬁc did not impact the number of live insects. However, when the heterospeciﬁc was not present, D. melacanthus caused lower pod production and increa- sed its growth rate. Diceraeus melacanthus was also the most tolerant species to imidacloprid compared to E. heros [RR 50 =15.32 (4.9-48.1)], and was the species that had the most enzymatic detoxiﬁcation when subjected to temperature changes (ie, 20 °C) with mortality at the LC 50 re- duced by 47.96%. Another result produced in this work was climate-based prediction models (i.e., ecological niche models). Model indicators were satisfactory for both species: for E. heros, the AUC (Area Under Curve) was 0.99 ± 0.01 and the TSS (True Skill Statistic) was 0.95 ± 0.03; for D. melacanthus, the AUC was 0.94 ± 0.04 and the TSS was 0.95 ± 0.03. Our forecast indicates greater potential damage from E. heros in the center-west of Brazil and in the west of Bahia, while D. melacanthus concentrates greater potential damage in the center-south of the country. This thesis then shows that despite the greater impact of D. melacanthus on pod reduction, E. heros was more competitive than D. melacanthus in the presence of both species, which justiﬁes its abundance; however, D. melacanthus may prove to be a major problem in the absence of E. heros. Furthermore, this study also showed the impact of insecticides on both species and in- dicates that some molecules may not be more effective at commonly used doses and that their detoxiﬁcation may be increased at low temperatures. Finally, we indicate, through ecological niche models, safe areas and areas with greater risks of soy and corn production against the attack of these insects. All studies carried out here suggest tools to be incorporated into a bed bug MIP program, helping with decision-making and contributing to the management of these pests in production ﬁelds. Keywords: Euschistus heros. Diceraeus (Dichelops) melacanthus. Enzymatic detoxiﬁcation. Inters- peciﬁc competition. Ecological niche modeling.